ПРОЕКТНА ТЕХНОЛОГІЯ В СИСТЕМІ ІННОВАЦІЙНОЇ ДІЯЛЬНОСТІ ВЧИТЕЛЯ (Педагогіка вищої та середньої школи, 2022)
The essence, leading ideas of project technology and ways of its usage in teacher's innovative activities are considered in the article.